PDZRN3 regulates adipogenesis of mesenchymal progenitors in muscle - Hiroki Iida; Minako Kawai-Takaishi; Yoshihiro Miyagawa; Yasuhiko Takegami; Akiyoshi Uezumi; Takeshi Honda; Shiro Imagama; Tohru Hosoyama (Regenerative Therapy)
Introduction: Intramuscular adipose tissue (IMAT) is frequently formed in certain pathological conditions, such as biological aging, and ectopic fat accumulation leads to muscle weakness and a subsequent decline in physical function. Although mesenchymal progenitors (MPs) are present in postnatal skeletal muscle and are the cells from which IMAT originates, the molecular mechanism by which MPs contribute to IMAT formation has not been completely elucidated. Recently, we found that PDZ domain-containing ring finger 3 (PDZRN3), an E3-ubiquitin ligase, was highly expressed in MPs. In this study, we aimed to clarify the functions of PDZRN3 in MPs and the roles of PDZRN3 in IMAT formation using in vitro and in vivo experiments. Methods: Primary mouse MPs isolated from hindlimb muscles were applied to adipogenic differentiation conditions, and expression fluctuation of PDZRN3 was verified with adipogenic differentiation and Wnt signaling markers. The role of PDZRN3 on MP’s adipogenesis was evaluated in vitro by gene knock-down experiments. To evaluate the contribution of PDZRN3 to IMAT formation in vivo, tamoxifen-inducible MP-specific Pdzrn3 knockout (Pdzrn3MPcKO) mice were developed. Results: PDZRN3 was more expressed in MPs than in muscle stem cells, and its expression profile of PDZRN3 fluctuated with the adipogenic differentiation of MPs. Our results revealed that PDZRN3 suppressed the adipogenesis of MPs in vitro through the activation of Wnt signaling and that a decrease in PDZRN3 accelerated adipogenesis. Indeed, IMAT significantly increased in the denervated muscles of Pdzrn3MPcKO mice. Conclusions: Our findings suggest that PDZRN3 is a key molecule in regulating IMAT formation. Since ectopic fat accumulation is frequently found in the skeletal muscles of older adults and also muscular dystrophy patients, PDZRN3 and its related pathways may represent a novel therapeutic target for these muscle pathologies.